Impact of MPO training and their experiences about the induction training: an assessment on Square Pharmaceuticals limited - Neha, Nishat Tabassum (Brac University, 2024)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2023.